2016
DOI: 10.1016/j.ebiom.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2a Randomized Clinical Trial: Safety and Post Hoc Analysis of Subretinal rAAV.sFLT-1 for Wet Age-related Macular Degeneration

Abstract: BackgroundWe present the results of a Phase 2a randomized controlled trial investigating the safety, and secondary endpoints of subretinal rAAV.sFLT-1 gene therapy in patients with active wet age-related macular degeneration (wAMD).MethodsAll patients (n = 32), (ClinicalTrials.gov; NCT01494805), received ranibizumab injections at baseline and week 4, and thereafter according to prespecified criteria. Patients in the gene therapy group (n = 21) received rAAV.sFLT-1 (1 × 1011 vg). All patients were assessed ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 31 publications
1
103
0
Order By: Relevance
“…When compared to the two control patients who were treated with ranibizumab, one patient required five rescue injections while the other patient was not able to be evaluated because of a vitreomacular traction . The results of the phase II clinical trial served to confirm the results from the phase I trial; however, no significant new results were shown …”
Section: Ocular Diseases Targeted By Aav Gene Therapy In Humansmentioning
confidence: 91%
See 1 more Smart Citation
“…When compared to the two control patients who were treated with ranibizumab, one patient required five rescue injections while the other patient was not able to be evaluated because of a vitreomacular traction . The results of the phase II clinical trial served to confirm the results from the phase I trial; however, no significant new results were shown …”
Section: Ocular Diseases Targeted By Aav Gene Therapy In Humansmentioning
confidence: 91%
“…108 The results of the phase II clinical trial served to confirm the results from the phase I trial; however, no significant new results were shown. 109 VEGF is also being targeted in a currently recruiting phase I clinical trial, sponsored by Regenxbio. They are evaluating the safety and tolerability of RGX-314, an AAV8 vector that encodes a soluble anti-VEGF protein (NCT03066258).…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…AAV has numerous natural serotypes with somewhat different viral capsid sequences and tissue tropisms, indicating that differences in the viral capsid proteins can lead to differences in infectivity. As a non-integrating virus with a strong safety record, AAV has strong promise as a clinical gene delivery vehicle, and as mentioned above there are numerous examples of strong proof of concept in clinical trials as well as a regulatory approval in the European Union [19]. …”
Section: Therapeutic Gene Editingmentioning
confidence: 99%
“…The last of these is the basis for a clinically approved gene therapy product in the European Union, and it is anticipated that a gene therapy for LCA2 may be approved in the US in 2017. In addition, early-stage clinical trials have demonstrated some positive signs in harnessing AAV to treat more complex disorders, such as overexpressing SERC2A in heart failure patients [8] and expressing the VEGF inhibitor sFLT-1 in patients with age-related macular degeneration [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report the use of soluble FMS-like tyrosine kinase-1 (sFLT-1), a naturally occurring VEGF inhibitor, coupled with an AAV delivery vector for sustained VEGF inhibition in the retina, hence negating the need for frequent anti-VEGF injections. [17][18][19] In AAV gene therapy, the effective expression of the transgene is contingent on the integration of the genetic material into the host genome of terminally differentiated and nondividing cells. In the context of AAV-mediated gene therapy for retinal diseases, this has previously been achieved via a subretinal injection to ensure close proximity of the vector with the cells that require transfection.…”
mentioning
confidence: 99%